The Role of the Adjudication Committee in Implementation Complete Systematic Land Registration (PTSL) In Keerom Regency - Eddy Pelupessy (Journal of Law, Politic and Humanities, 2024)
This research was carried out because until now there is a lot of land that has not been certified and disputes often occur in Keerom Regency. In addition, a systematic land registration process is very important to create orderly land law and ensure legal certainty. This study aims to determine the role played by the Adjudication Committee in carrying out complete systematic land registration in Keerom Regency as well as the obstacles faced by the Adjudication Committee in doing so. In this research, normative and empirical juridical are used. This means laws, literary materials, written regulations, and ways of identifying and conceptualizing law as an actual social institution in real life systems. This research shows that the adjudication committee plays an important role in carrying out comprehensive and systematic land registration in Keerom Regency. This is shown by the large number of lands that have been certified during the land registration process. This will automatically reduce the number of land disputes because residents already have certificates as proof of land ownership. To carry out complete systematic land registration in Keerom Regency, there are three factors that become obstacles. The first is the announcement of physical and juridical data; the second is the challenge of applying the contradiction principle of delimitation; and the third is proof of rights.